Relationship between production and reproduction in 5,480 Holstein herds enrolled in the Midstates Processing Center. - Call, Edward P.; Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station, 2012)
Reproductive parameters were evaluated in 5,480 Holstein herds involving 335,673 cows to determine the reported negative genetic effect of production on reproduction. While higher producing herds had a slight decline in days to first bred, this effect was offset by a similar increase in services per conception. The greatest effect was seen in the percent of cows open and the average days open. It was concluded that managers of higher producing herds are more aware of the need to get cows bred back after calving and implement the necessary practices to minimize the percent of cows not yet serviced and the average days open. The negative genetic relationship between production and reproduction may be overcome with sound management practices.
Keywords: Dairy; Production; Reproduction; Performance; Conception